Agronomic Traits of Direct-Seeded Rice (Oryza sativa) Applied with Microbial Inoculants and Varying Fertilizer Levels - Inocencio, Leo G.; Edaño, Ma. Lourdes; Sta. Cruz, Pompe; Ocampo, Eureka Teresa; Sanchez, Pearl (Biosaintifika: Journal of Biology & Biology Education, 2025)
The study was conducted to evaluate the effects of microbial inoculants and nutrient levels on the agronomic performance of dry direct-seeded NSIC Rc192 rice under aerobic conditions. Six biofertilizer treatments (control, Bio-N, BioGroe, Mykovam, MykoPlus, and Avatar) were combined with four nutrient levels (0 %, 25 %, 50 %, and 75 % NP + full K). The study aimed to assess the impact of these treatments on root colonization, tiller production, and overall plant growth. Root and soil colonization at 60 days after sowing (DAS) revealed that MykoPlus facilitated more effective root colonization than other inoculants. However, unfavorable environmental conditions, including high temperatures and moisture deficits, negatively impacted tiller production and grain yield. Despite these challenges, BioGroe showed the most promise, significantly enhancing root development and tiller count, particularly when combined with 50 % NP + full K. The study concluded that microbial inoculants, especially BioGroe, can improve rice growth under aerobic conditions, but environmental factors are crucial in determining their effectiveness. Further research is needed to optimize these inoculants for varying environmental conditions to maximize their benefits in rice cultivation.